Acute Cardiorespiratory and Metabolic Responses During Resistance Exercise In The Lactate Threshold Intensity - de Sousa, N. M. F.; Magosso, R. F.; Pereira, G. B.; Souza, M.V. C.; Vieira, A.; Marine, D. A.; Perez, S.E. A.; Baldissera, V. (International Journal of Sports Medicine, 2012)
The aims were both to determine lactate and ventilatory threshold during incremental resistance training and to analyze the acute cardiorespiratory and metabolic responses during constant-load resistance exercise at lactate threshold (LT) intensity. Ten healthy men performed 2 protocols on leg press machine. The incremental test was performed to determine the lactate and ventilatory thresholds through an algorithmic adjustment method. After 48 h, a constant-load exercise at LT intensity was executed. The intensity of LT and ventilatory threshold was 27.1±3.7 and 30.3±7.9% of 1RM, respectively (P=0.142). During the constant-load resistance exercise, no significant variation was observed between set 9 and set 15 for blood lactate concentration (3.3±0.9 and 4.1±1.4 mmol.L − 1, respectively. P=0.166) and BORG scale (11.5±2.9 and 13.0±3.5, respectively. P=0.783). No significant variation was observed between set 6 and set 15 for minute ventilation (19.4±4.9 and 22.4±5.5 L.min − 1, respectively. P=0.091) and between S3 and S15 for VO2 (0.77±0.18 and 0.83±0.16 L.min − 1, respectively. P=1.0). Constant-load resistance exercise at LT intensity corresponds to a steady state of ventilatory, cardio-metabolic parameters and ratings of perceived exertion.
Keywords: anaerobic threshold; resistance training; steady state; leg press